Carcass Composition, Meat Quality, Calpain Activity, Fatty Acid Composition and Ribonucleotide Content in Southern Thai Native Goats and Three-Way Crossbred Goats - Chanporn Chaosap; Nantana Chauychuwong; Ratchasak Chauychuwong; Chatchai Sriprem; Panneepa Sivapirunthep; Awis Qurni Sazili (My University, 2021)
Carcass composition, meat quality, calpain activity, fatty acid composition, and ribonucleotide content were examined and compared between male Southern Thai native goats (NG, n = 10) and three-way crossbred goats (CG, 50% Boer × 25% Saanen × 25% Southern Thai native, n = 10). All animals were fed 1.5% body weight of concentrate (16% protein and 70% total digestible nutrients) and fresh Napier grass for 4 months. At the end of raising period, the final weight between the two genotypes was not significantly different. The percentage of carcass, bone, and fat of CG were higher than those of NG. NG presented lower shear force values, insoluble and total collagen content but higher collagen solubility and calpain-1 activity at 24 h postmortem. Additionally, NG meat was high in monounsaturated fatty acids but low in saturated fatty acids. However, the amount of ribonucleotide was no significant difference between two genotypes.
Keywords: Meat and Animal Product Quality